Social Safety Theory: Understanding social stress, disease risk, resilience, and behavior during the COVID-19 pandemic and beyond - Slavich, George M. (Current opinion in psychology, 2022)
Many of life's most impactful experiences involve either social safety (e.g., acceptance, affiliation, belonging, inclusion) or social threat (e.g., conflict, isolation, rejection, exclusion). According to Social Safety Theory, these experiences greatly impact human health and behavior because a fundamental goal of the brain and immune system is to keep the body biologically safe. To achieve this crucial goal, social threats likely gained the ability to activate anticipatory neural-immune responses that would have historically benefited reproduction and survival; the presence of social safety, in turn, likely dampened these responses. Viewing positive and negative social experiences through this lens affords a biologically based evolutionary account for why certain stressors are particularly impactful. It also provides an integrated, multi-level framework for investigating the biopsychosocial roots of psychopathology, health disparities, aging, longevity, and interpersonal cognition and behavior. Ultimately, this work has the potential to inform new strategies for reducing disease risk and promoting resilience. •Social Safety Theory posits that developing and maintaining friendly social bonds is critical.•Social conflict, rejection, and exclusion historically increased risk for injury and infection.•Therefore, anticipatory neural-immune reactivity to social threat was likely highly conserved.•This multi-level response to social threat is critical for reproductive success and survival.•However, it also increases peoples' risk for viral infections and inflammatory diseases.